Experimental study on premixed flame propagation of hydrogen/methane/air deflagration in closed ducts. (23rd February 2017) - Zheng, Kai; Yu, Minggao; Zheng, Ligang; Wen, Xiaoping; Chu, Tingxiang; Wang, Liang
Abstract: Experimental investigations of premixed hydrogen/methane/air flame propagation in closed ducts were conducted in six ducts for stoichiometric mixtures with five hydrogen fractions (i.e., 0%, 25%, 50%, 75%, and 100%). In the experiments, the flame propagation behavior associated with the pressure dynamic was studied, and the results show that the flame shape changes as the aspect ratio and hydrogen fraction vary. In the duct with the smallest aspect ratio, only the first four stages of the "tulip" flame were observed. As the aspect ratio increased, the flame structure evolved differently. In cases with lower hydrogen fractions, the flame front became asymmetric, and the lower lateral lip propagated slower than the upper one in a classic "tulip" flame inversion. As the hydrogen fraction increased but before reaching pure hydrogen, the flame propagated while maintaining its tulip shape, accompanied by small oscillations; furthermore, a cellular flame appeared in the duct with the largest aspect ratio before the end of propagation. In those ducts, a distorted "tulip" flame with indented tulip lips was observed for pure hydrogen. For all configurations, the flame speed dynamic is closely related to the pressure, and they both significantly increase with increasing hydrogen. Highlights: The premixed flame propagation of hydrogen/methane mixtures in closed ducts has been studied. The flame shape evolves differently as the aspect ratio and hydrogen fraction increase. Both the maximum flame speed and maximum pressure increase greatly with the hydrogen addition. The flame speed dynamic is closely related to the pressure.